Afghanistan Long War, Forgotten Peace - Cox, Michael (LSE Press, 2022)
Afghanistan has been in the headlines for many years - but tragically for all the wrong reasons. First invaded by the Soviets in 1979, the country then experienced the trauma of civil war followed by yet another intervention, this time by the United States and allies, which ended with the West's ignominious withdrawal in August 2021. Afghanistan: Long War, Forgotten Peace examines multiple dimensions of what happened and why, and what the future holds for the country now the Taliban are back in power. Multidisciplinary in approach, this book features analysts from a variety of academic disciplines, including policy-makers and public intellectuals - many with direct experience of having lived and worked in Afghanistan. It explains why the Taliban finally triumphed, what this means for Afghan society, and how competing actors in the international system have reacted to the Taliban takeover. Questions include whether the West's withdrawal represented a major or only a temporary setback for NATO and the United States, and whether and how there can be any amelioration of the situation in Afghanistan itself. The country and its people face multiple interrelated challenges, including those of women's rights, the drugs economies and human trafficking and exploitation. This volume is essential reading for all those concerned with what happens in Afghanistan over the coming months and years, the consequences for the Afghan people - and for the rest of the world.